Algorithm as a Pattern of Kampung : Case Study: Cilincing Fisherman Village - husin, Denny; Komala, Olga Nauli (Border: Jurnal Arsitektur, 2024)
Fisherman Village is one of the Jakarta informalities that has been growing with the city since its former role as a port city. This phenomenon not only contributes to the city’s economic value but also to its overall dynamic sectors. Its existence confirms the important role of its built environment; the research objective is to reveal the kampung pattern for preserving and developing this kampung. Unlike other urban grains, this kampung consists of naval and maritime qualities, despite general critique towards environmental and spatial conditions. The morphology is utilized to detect its architectural form; thus, its algorithm can be extracted through QGIS, steps are: 1) mapping, 2) massing, and 3) algorithm. QGIS converts mapping into a massing series, unraveling the geometry of the kampung house silhouette as an algorithm pattern. The outcome is Kampung’s algorithm pattern. The discovery involves nautical and maritime influences, while the originality is the Kampung Cilincing order formula. This research promotes a specific housing unit and type as a local potency to stimulate the development of Kampung’s module guideline. The dominant type can be used for typical replication while questioning the recessive type to stimulate innovation as a guide.